Nursing Students' Experiences of Using Adobe Connect in a First-year Professional Nursing Course - Ditzel, Liz Mary; Wheeler, Anna (International Journal of Learning, Teaching and Educational Research, 2017)
This paper reports the survey results of first-year Bachelor of Nursing students' (n=88) experiences using Adobe Connect in a Professional Nursing course. Data were analysed using descriptive statistics and themes were coded from responses to open-ended survey questions. Quantitative data affirmed the learning and teaching benefits of using Adobe Connect and identified areas for improvement. Qualitative data indicated that accessing and using Adobe Connect from the comfort of home was greatly appreciated. Negative aspects related to feeling a lack of involvement, and poor digital audio and visual quality, mainly due to Internet delivery problems. These findings indicate that this technology suits the learning needs of first-year students. Used in combination with a limited number of face-to-face tutorials, students have the 'best of both worlds' – home-based, selfpaced learning, access to recorded lectures, adequate peer/teacher contact time and successful course results. https://doi.org/10.26803/ijlter.16.9.9